Beta testing an educative experience with artificial intelligence: Immaturity and growth in a Deweyan view - Baldonado, Sophia Ysabelle Creselda Bunol (Animo Repository, 2025)
Society is now in the era of an Education 4.0 which focuses on the active role of technology as part of the transformation of the future of education. This highlights the inevitable integration of artificial intelligence in our everyday lives, especially in learning. Academics have treated AI as a medium to directly address issues and gaps found in education but, these discussions continue to face the risks and harms of a technological advancement that is continuously evolving. We must consider approaching this relationship by understanding the role of education, or rather the actions it must take moving forward which can be developed by lifelong learning. John Dewey would assert that although there is no exact culmination to learning, the closest we could achieve to an all-inclusive end to education is more growth. This can address the concern between AI and education whereas, by continuously learning and exposing oneself on the subject-matter, will enable society to better prepare for a future fully immersed in this technological innovation. In preparation for it, there must be an understanding between AI natives (mature members) and non-AI natives (immature members) since the gaps they raise will allow society to grow. This growth can be achieved by educative experiences. Thus, this paper claims that there exists an educative experience despite the existence of artificial intelligence. Dewey’s conditions for growth and experience are realized in society by AI natives who represent the mature members of society in this age. The gaps in communication between mature and immature citizens can be actualized by engaging non-AI natives in this current environment. Not only will this improve the quality of education but also, allow society to progress towards a future with technology by its side.